Pendidikan Kesehatan Tentang Latihan ROM (Range of Motion) Meningkatkan Pengetahuan dan Keterampilan Keluarga Penderita Stroke - Mira Utami Ningsih; Nurunniswati Nurunniswati; Mas'adah Mas'adah; Cembun Cembun; A'an Dwi Sentana; Mardiatun Mardiatun (Poltekkes Kemenkes Mataram, 2022)
Stroke is an important disease to overcome because of its high prevalence and tends to continue to increase and its impact that can cause disability to death. The condition of stroke is often a chronic condition, that requires continued treatment at home. Family is an important component in the recovery process of a patient, including stroke survivors. The task of care that was previously mostly the responsibility of health workers at the hospital, has turned into a family health task. Families can help the rehabilitation process by helping the stroke patients perform ROM exercises. However, most families do not have adequate knowledge and skills about ROM exercises. This study aims to identify the effect of providing health education about ROM exercises on the knowledge and skills of families of stroke survivors at home. This research is pre-experimental research, with a one group pre-test-post-tests design. The sample is the family of stroke patients who are treated at home. Knowledge and skills were measured using questionnaires and checklists. The results of paired t-test on knowledge and skills before and after health education showed the effect of health education on increasing family knowledge and skills (ρ – value = 0.000; = 0.05). Health education about ROM needs to be performed routinely and repeatedly as part of the rehabilitation of stroke patients at home. Future research needs to focus on the correlation between family knowledge about ROM and the improvement of muscle strength in stroke patients at home.